Points . . . : interviews, 1974-1994 - Derrida, Jacques (Meridian (Stanford, Calif.), 1995)
This volume collects twenty-three interviews given over the course of the last two decades by Jacques Derrida. It illustrates the extraordinary breadth of his concerns, touching upon such subjects as the teaching of philosophy, sexual difference and feminine identity, the media, AIDS, language and translation, nationalism, politics, and Derrida's early life and the history of his writings. Often, as in the interview on Heidegger, or that on drugs, or on the nature of poetry, these interviews offer not only an introduction to other discussions, but something available nowhere else in his work.